2023
DOI: 10.26555/humanitas.v20i1.138
|View full text |Cite
|
Sign up to set email alerts
|

Job crafting and innovative behavior among hospitality workers: The moderation effect of work engagement

Abstract: The COVID-19 pandemic impacted a decline in hotel occupancy rates in the hospitality sector worldwide, including in Indonesia. Therefore, hotel management and workers need innovation to attract customers by crafting their jobs and developing original and creative ideas. Moreover, employees’ work engagement will also support the emergence of innovative behavior. This study aimed to explore whether work engagement moderates the relationship between job crafting and innovative work behavior among hotel employees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…However, it is not in line with the proactive attitude of the employees who have a value that is below average (0.794), so even if employees learn new things but do not apply them through a proactive attitude, they will not have innovative work behavior. The results of this study truly show differences in results with the previous studies which state that job crafting has a positive effect on innovative work behavior (Afsar et al, 2019;Kaur & Rahmadani, 2023;Pradana & Suhariadi, 2020).…”
Section: The Effect Of Job Crafting On Innovative Work Behaviorcontrasting
confidence: 98%
See 1 more Smart Citation
“…However, it is not in line with the proactive attitude of the employees who have a value that is below average (0.794), so even if employees learn new things but do not apply them through a proactive attitude, they will not have innovative work behavior. The results of this study truly show differences in results with the previous studies which state that job crafting has a positive effect on innovative work behavior (Afsar et al, 2019;Kaur & Rahmadani, 2023;Pradana & Suhariadi, 2020).…”
Section: The Effect Of Job Crafting On Innovative Work Behaviorcontrasting
confidence: 98%
“…Previous studies have described several factors that influence innovative work behavior, including 1) The study by Afsar et al (2019) and Kaur and Rahmadani (2023) regarding employee behavior in the hospitality sector, stating that job crafting affects innovative work behavior positively and significantly;…”
Section: Introductionmentioning
confidence: 99%
“…While Li et al (2024) found that facilitating conditions, self-efficacy, and job engagement have significant direct effects on elementary mathematics teachers' IWB. Findings by Kaur and Rahmadani (2023) also confirm that job engagement directly affects IWB. Additionally, job engagement mediates the relationship between job crafting and innovative work behavior (Bhattarai & Budhathoki, 2023).…”
Section: Discussionmentioning
confidence: 53%
“…This aligns with the findings of studies by Anzarwati (2021), Bawuro et al (2019), andArasli &Alphun (2019), collectively establishing that IWB is significantly and positively influenced by intrinsic motivation. However, intrinsic motivation also plays an intermediate role between leadership and innovative work behavior, as it boosts the creativity of employees (Kaur & Rahmadani, 2023).…”
Section: Discussionmentioning
confidence: 99%